MAKNA TUTURAN RITUAL DOANG KOA PADA KELOMPOK ETNIK KEDANG DI KECAMATAN BUYASURI KABUPATEN LEMBATA - Karolus Budiman Jama; Anastasia Dulang (Jurnal Lazuardi, 2022)
"The Meaning of Doang Koa Ritual Speech in the Kedang ethnic group in Buyasuri District, Lembata Regency". This study aims to describe the meaning of ritual speech doang koa in the Kedang ethnic group in Buyasuri District, Lembata Regency, using Roland Barthez's theory of Semiotics by emphasizing: (1) sign denotation that produces meaning directly through basic images captured by the five senses, (2) sign connotations that present cultural meaning due to cultural construction, (3) sign myths that interpret meanings that naturalize a belief. The method used in this study is a qualitative descriptive method. Qualitative descriptive research method is a research that provides an objective, systematic, and factual picture according to data related to the research focus without using statistical principles. The results showed that the meaning of the ritual speech doang koa is a form of request for self-purification and protection to the highest form of Ula Loyo Ero Au through the intercession of ancestors as a feature of family ties and relationships of living together that are not broken even by death.